Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4103/0970-9185.119151
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of intrathecal dexmedetomidine, clonidine, and fentanyl as adjuvants to hyperbaric bupivacaine for lower limb surgery: A double blind controlled study

Abstract: Background:Various adjuvants are being used with local anesthetics for prolongation of intraoperative and postoperative analgesia. Dexmedetomidine, the highly selective 2 adrenergic agonist is a new neuraxial adjuvant gaining popularity.Settings and Design:The study was conducted in prospective, double blind manner. It included 120 American Society of Anesthesiology (ASA) class I and II patients undergoing lower limb surgery under spinal anesthesia after approval from hospital ethics committee with written and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

35
132
8
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(186 citation statements)
references
References 22 publications
35
132
8
1
Order By: Relevance
“…It has an added advantage because, if the sensory block is achieved earlier at T6 dermatome, surgery can also be started earlier in group II as compared with group I. Previously it was also observed that time taken for regression of sensory block to S1 dermatome was delayed with the addition of dexmedetomidine to bupivacaine [12,[16][17][18] , which is in accordance with the present study. Complete motor blockade was achieved earlier and the duration of motor block was more prolonged in group II as compared with group I.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…It has an added advantage because, if the sensory block is achieved earlier at T6 dermatome, surgery can also be started earlier in group II as compared with group I. Previously it was also observed that time taken for regression of sensory block to S1 dermatome was delayed with the addition of dexmedetomidine to bupivacaine [12,[16][17][18] , which is in accordance with the present study. Complete motor blockade was achieved earlier and the duration of motor block was more prolonged in group II as compared with group I.…”
Section: Discussionsupporting
confidence: 80%
“…It has also been observed earlier that addition of low-dose dexmedetomidine to intrathecal bupivacaine does not lead to higher sedation scores [12,13] . Patients remained hemodynamically stable in both groups at all measured intervals for 24 h. Dexmedetomidine as an adjuvant to bupivacaine does not produce any significant hemodynamic changes and vitals remained stable both intraoperatively and postoperatively [16][17][18] . Incidence of side effects and complication was comparable between the two groups, which is in accordance with previous studies [13,19] ..…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9) Several studies have shown that use of intrathecal dexmedetomidine as an adjuvant to hyperbaric bupivacaine is associated with prolonged motor and sensory block, while maintaining the hemodynamic stability. [25][26][27] Recent studies have shown that dexmedetomidine may be safely used as an intrathecal supplement in Cesarean delivery. 12,28) Respiratory depression is a potential side effect of dexmedetomidine.…”
Section: Discussionmentioning
confidence: 99%
“…13,28) The intrathecal doses of dexmedetomidine used in our study were based on previous human studies wherein no neurotoxic effects were documented at these doses. [25][26][27][33][34][35] A limitation of this study was that a doseresponse experiment was not performed to determine the optimal dose of dexmedetomidine required for optimal suppression of shivering, but without causing any significant side effects. In the present study, dexmedetomidine was used as an adjuvant to hyperbaric bupivacaine in a dose of 5 µg as this dosage is reported to be associated with prolonged duration of sensory and motor block without significant side effects.…”
Section: Discussionmentioning
confidence: 99%